Studying the role of fascin-1 in mechanically stressed podocytes - Kliewe, Felix; Scharf, Christian; Rogge, Henrik; Darm, Katrin; Lindenmeyer, Maja T.; Amann, Kerstin Ute; Cohen, Clemens D.; Endlich, Karlhans; Endlich, Nicole (Scientific Reports, 2017)
Glomerular hypertension causes glomerulosclerosis via the loss of podocytes, which are challenged by increased mechanical load. We have demonstrated that podocytes are mechanosensitive. However, the response of podocytes to mechanical stretching remains incompletely understood. Here we demonstrate that the actin-bundling protein fascin-1 plays an important role in podocytes that are exposed to mechanical stress. Immunofluorescence staining revealed colocalization of fascin-1 and nephrin in mouse kidney sections. In cultured mouse podocytes fascin-1 was localized along actin fibers and filopodia in stretched and unstretched podocytes. The mRNA and protein levels of fascin-1 were not affected by mechanical stress. By Western blot and 2D-gelelectrophoresis we observed that phospho-fascin-1 was significantly downregulated after mechanical stretching. It is known that phosphorylation at serine 39 (S39) regulates the bundling activity of fascin-1, e.g. required for filopodia formation. Podocytes expressing wild type GFP-fascin-1 and non-phosphorylatable GFP-fascin-1-S39A showed marked filopodia formation, being absent in podocytes expressing phosphomimetic GFP-fascin-1-S39D. Finally, the immunofluorescence signal of phosphorylated fascin-1 was strongly reduced in glomeruli of patients with diabetic nephropathy compared to healthy controls. In summary, mechanical stress dephosphorylates fascin-1 in podocytes in vitro and in vivo thereby fascin-1 may play an important role in the adaptation of podocytes to mechanical forces.
EVALuna2:25547